HIV-1 gp120 and Drugs of Abuse: Interactions in the Central Nervous System - Silverstein, Peter S. (2012)
HIV-1 infection is a global public health problem with more than 34 million people living with HIV infection. Although great strides have been made in treating this epidemic with therapeutic agents, the increase in patient life span has been coincident with an increase in the prevalence of HIV-associated neurocognitive disorders (HAND). HAND is thought to result from the neurotoxic effects of viral proteins that are shed from HIV-infected microglial cells. One of the primary neurotoxins responsible for this effect is the HIV-1 glycoprotein gp120. Exposure of neurons to gp120 has been demonstrated to cause apoptosis in neurons, as well as numerous indirect effects such as an increase in inflammatory cytokines, an increase in oxidative stress, and an increase in permeability of the blood-brain barrier. In many patients, the use of drugs of abuse (DOA) exacerbates the neurotoxic effects of gp120. Cocaine, methamphetamine and morphine are three DOAs that are commonly used by those infected with HIV-1. All three of these DOAs have been demonstrated to increase oxidative stress in the CNS as well as to increase permeability of the blood-brain barrier. Numerous model systems have demonstrated that these DOAs have the capability of exacerbating the neurotoxic effects of gp120. This review will summarize the neurotoxic effects of gp120, the deleterious effects of cocaine, methamphetamine and morphine on the CNS, and the combined effects of gp120 in the context of these drugs.